Pengaruh Inklusi Keuangan dan Edukasi Terhadap Keputusan Perilaku Penggunaan QRIS: Studi Kasus Mahasiswa Manajemen UBP Karawang 2021 - Tria Melani; Ujang Suherman; Rengga Madya Pranata (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of financial inclusion and education on behavioral decisions to use the Quick Response Code Indonesian Standard (QRIS) among Management students of Buana Perjuangan University, Karawang, class of 2021. The study used a descriptive quantitative approach with data collection through questionnaires from 80 respondents selected using the simple random sampling method. The analysis was carried out using multiple linear regression. The results of the study showed that financial inclusion had a significant influence on QRIS usage behavior. This indicates that adequate access to financial services and knowledge of financial products increase the decision to use QRIS. Education was also shown to have a significant influence, where students' understanding of digital transaction security and involvement in educational programs encouraged confidence in using QRIS. Simultaneously, both variables contributed 46% to behavioral decisions to use QRIS. The implication of this study is the need for educational institutions and financial service providers to improve digital financial literacy through structured educational programs and expand access to financial services. This step is expected to support the adoption of QRIS and a more inclusive digital transformation of finance